Space solar-power station, wireless power transmission, and biological implications. - Lin, James C. (IEEE Antennas & propagation magazine.)
Discusses the history of the concept of power generation on a satellite and its transmission to the surface of the Earth. The implications for human health are considered together with means for alleviating possible health risks.